Standardization of 96% Ethanol Extract of Beluntas Leaves, Kenikir Leaves, and Purple Corn Kernels - Riwanti, Pramudita; Ma'arif, Burhan; Primadini, Filicia Regya; Maulidiah, Erika Nur; Ramadhan, Ravy Irsyad (Jurnal Jamu Indonesia, 2025)
Beluntas (Pluchea indica) leaves, kenikir (Cosmos caudatus) leaves, and purple corn (Zea mays) kernels have the potential to be developed into preparations of traditional medicine, which requires standardization of raw materials. The 96% ethanol extract P. indica leaves from Batu, C. caudatus leaves from Wonosari, and purple corn kernels from Sukabumi have been standardized. Both specific and non-specific requirements are covered. Fragment identifiers of P. indica leaves, such as stomata and trichoma. C. caudatus leaves, such as vascular tissue with stair thickening and multicellular hair covering. Purple corn kernels such as amylum and hilum in the form of stars. The thick extracts were obtained from the results of ultrasonic-assisted extraction with yields of 14.76% for P. indica leaves, 7.49% for C. caudatus leaves, and 5.79% for purple corn kernels. The organoleptic of ethanolic extract P. indica leaves is thick and greenish-black, C. caudatus leaves is thick and brown, and purple corn kernels is thick and purple. The water-soluble content from P. indica leaves, C. caudatus leaves, and purple corn kernels was 13.85%, 11.13%, and 10.62%, respectively. The ethanol soluble content was 16.58%, 14.87%, and 15.89%. The total ash content for P. indica leaves, C. caudatus leaves, and purple corn kernels was 15.04%, 9.37%, and 4.76%. The percentage of water content was 9.07%, 14.34%, and 11.12%. The standardized data collected was compared with the requirements in the official monographs of Materia Medika Indonesia and Farmakope Herbal Indonesia. The results showed that the three samples used had met most of the standardization parameters and could be developed into traditional medicine.